2021
DOI: 10.3310/hsdr09230
|View full text |Cite
|
Sign up to set email alerts
|

STOPP/START interventions to improve medicines management for people aged 65 years and over: a realist synthesis

Abstract: Background Drug-related problems and potentially inappropriate prescribing impose a huge burden on patients and the health-care system. The most widely used tools for appropriate prescription in older adults in England and in other European countries are the Screening Tool of Older People’s Prescriptions (STOPP)/Screening Tool to Alert to the Right Treatment (START) tools. STOPP/START tools support medicines optimisation for older adults. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Generally, minimal information was given on how advisory group members were recruited. For example, Wade et al [29] explained their youth advisory group was formed by “advertising through batyr, a for‐purpose preventative mental health organization in Australia.” Those that did give information described sending invitations to existing PPI groups [26, 45] or using a pre‐established advisory group panel from a wider study, supplemented with additional stakeholders [57]. In contrast, one review [27] reported actively trying to recruit outside of established PPI groups to engage with new points of view.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, minimal information was given on how advisory group members were recruited. For example, Wade et al [29] explained their youth advisory group was formed by “advertising through batyr, a for‐purpose preventative mental health organization in Australia.” Those that did give information described sending invitations to existing PPI groups [26, 45] or using a pre‐established advisory group panel from a wider study, supplemented with additional stakeholders [57]. In contrast, one review [27] reported actively trying to recruit outside of established PPI groups to engage with new points of view.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 provides a flowchart of the screening process and documents reasons for exclusion. 40% ( n = 37) of the realist reviews cited use of an advisory group at some stage (as per the working definition for this study, notably other terminology was often reported) [14–17, 25–61]. 60% ( n = 56) did not mention the use of an advisory group [62–117].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of polypharmacy in particular is highly relevant, as polypharmacy poses a risk for patients since not all prescribed medications are necessarily appropriate. Several methods have been developed to detect such inappropriate medication; however, it is essential to keep in mind the influence of the number of medications alone on self-reported medication use [ 42 , 43 , 44 ], to detect potentially harmful medication regimes.…”
Section: Discussionmentioning
confidence: 99%